2018
DOI: 10.1038/s41598-018-30833-8
|View full text |Cite
|
Sign up to set email alerts
|

HbA1c Measured in the First Trimester of Pregnancy and the Association with Gestational Diabetes

Abstract: We aimed to examine the prospective association between first trimester HbA1c and gestational diabetes (GDM) and explore the utility of HbA1c for prediction of GDM. We used data from a case-control study within the prospective NICHD Fetal Growth Studies-Singleton Cohort (2009–2013), which enrolled 2,802 women at 12 U.S. clinical centers. HbA1c was measured in GDM cases (n = 107) and matched controls (n = 214) targeted at 8–13, 16–22, 24–29, and 34–37 gestational weeks. We excluded women with HbA1c ≥ 6.5% (48 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 27 publications
(22 reference statements)
1
33
0
Order By: Relevance
“…There has been a lack of consistency in the identification of markers that predict GDM 26–28. We found that higher HOMA-IR or C-peptide or insulin or glucose concentration determined at ~16 weeks’ gestation was associated with 2.7-fold to 4.4-fold increased risk for developing GDM independent of several traditional risk factors, including maternal age and BMI.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There has been a lack of consistency in the identification of markers that predict GDM 26–28. We found that higher HOMA-IR or C-peptide or insulin or glucose concentration determined at ~16 weeks’ gestation was associated with 2.7-fold to 4.4-fold increased risk for developing GDM independent of several traditional risk factors, including maternal age and BMI.…”
Section: Discussionmentioning
confidence: 80%
“…We found that higher HOMA-IR or C-peptide or insulin or glucose concentration determined at ~16 weeks’ gestation was associated with 2.7-fold to 4.4-fold increased risk for developing GDM independent of several traditional risk factors, including maternal age and BMI. Recently, in a secondary analysis of case–control study, Hinkle et al reported that elevated HbA 1c levels at 8–13 weeks’ gestation were associated with GDM 26. Another study reported that HOMA-IR at week 7–12 gestation was associated with GDM 27.…”
Section: Discussionmentioning
confidence: 99%
“…In a study involving 413 predominantly Hispanic women in California, the adjusted OR for women with HbA1c-FT in the 5.7-6.4 (39-46 mmol/l) range was 2.54, compared with those with a level <5.7% (39 mmol/l) [19]. A recent case control study from the United States, involving 107 women with GDM and 214 matched controls, has reported a 22% increase in adjusted GDM risk with each 0.1% (1 mmol/l) increase in HbA1c-FT [36]. In contrast, a study from Philadelphia in 250 women of predominantly Caucasian origin did not confirm first trimester HbA1c-FT as a predictor of GDM (adjusted OR not significant) [33].…”
Section: Discussionmentioning
confidence: 98%
“…However, Hinkle et al recently demonstrated that regardless of subsequent GDM diagnosis, hemoglobin A1c decreases until approximately 16 to 22 weeks of gestation of pregnancy. 27 Therefore, despite the difficulty in hemoglobin A1c interpretation due to the physiologic responses to pregnancy (e.g., hemodilution with increases in plasma volume, increased erythrocyte production and turnover, natural insulin resistance of pregnancy), women without pregestational diabetes, but with a first trimester hemoglobin A1c of 5.7 to 6.4% are highly likely to represent prediabetes. Second, there are a limited number of studies for review, some of the included studies were limited by small sample size, and the number of quality studies was inadequate to perform a meta-analysis, which is currently the gold standard.…”
Section: Discussionmentioning
confidence: 99%